Peran Konfusianisme terhadap Counterfeiting di China pada Rezim Hu Jintao - Ardiansyah Fabrin, Faisal Aldi; Windiani, Reni; Puspapertiwi, Sheiffi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
This study aims to determine the persistence of counterfeiting in China which is also calledshanzhai in Hu Jintao regime. This study also provides an overview of the factors thataffect the persistence of counterfeiting or shanzhai in China. This study uses the theory ofconstructivism, which draws conclusions and from the data collected in the field. Theresults of this study indicate that in the regime of Hu Jintao, a change in the role of newidentity in China is a capitalist communist who will create a policy that gave birth shanzhaiin China. And the norm adopted by the Chinese community is Confucianism which latercan affect the counterfeiting in China. In the norms of Confucianism adopted by thisChinese society, do not prohibit the existence of counterfeiting due to counterfeiting issomething that does not violate the norm. Thus, both of these have an effect on the lessefficient and less effective enforcement of intellectual property rights in China.